2010
DOI: 10.1016/j.stem.2010.11.016
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-Resident Adult Stem Cell Populations of Rapidly Self-Renewing Organs

Abstract: The epithelial lining of the intestine, stomach, and skin is continuously exposed to environmental assault, imposing a requirement for regular self-renewal. Resident adult stem cell populations drive this renewal, and much effort has been invested in revealing their identity. Reliable adult stem cell biomarkers would accelerate our understanding of stem cell roles in tissue homeostasis and cancer. Membrane-expressed markers would also facilitate isolation of these adult stem cell populations for exploitation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
258
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 323 publications
(266 citation statements)
references
References 108 publications
(114 reference statements)
8
258
0
Order By: Relevance
“…Taken together, the findings from lineage tracing do not support a major input of stem cells in adult pituitary homeostatic turnover, which is in line with findings in other 'lazy' tissues (Barker et al 2010;Huch et al 2013a,b;Rando 2006;Slack 2008;Vankelecom 2012;Wabik and Jones 2015).…”
Section: Basal and Adapting Adult Pituitarysupporting
confidence: 66%
See 3 more Smart Citations
“…Taken together, the findings from lineage tracing do not support a major input of stem cells in adult pituitary homeostatic turnover, which is in line with findings in other 'lazy' tissues (Barker et al 2010;Huch et al 2013a,b;Rando 2006;Slack 2008;Vankelecom 2012;Wabik and Jones 2015).…”
Section: Basal and Adapting Adult Pituitarysupporting
confidence: 66%
“…The tissue stem cells not only give rise to new specialized cells of the organ but must also perpetuate by producing at least one 'selfie.' Differentiation potential (ranging from uni-to multipotency) and selfrenewal capacity indeed represent the core hallmarks of adult tissue stem cells (Barker et al 2010;De Los Angeles et al 2015;Rando 2006;Wabik and Jones 2015). On the other hand, the degree of activity of adult stem cells is clearly dependent on the tissue.…”
Section: Pituitary Stem Cells: Expanding Molecular Portrayalmentioning
confidence: 99%
See 2 more Smart Citations
“…The lack of bone fide gastroesophageal stem cell markers has made it difficult to conclude absolutely that LRCs are stem cells. Antibodies to LGR5 are currently unreliable and lineage tracing from a single lgr5 stem cell has only been demonstrated in the murine pylorus 38 . Antibodies to musashi-1 have been shown to bind to parietal cells 39,40 and no lineage tracing from a musashi-1-positve cell has been published and studies using CD133 have only shown lineage tracing in the intestine not the upper gastrointestinal tract 41 .…”
Section: Discussionmentioning
confidence: 99%